The grotesque elements in Poe’s “Black Cat” and Scudder’s “The White Cat” - Endurance, Anegbe; Wan Yahya, Wan Roselezam; Majeed, Abdulhameed A. (Australian International Academic Centre, 2014)
The present essay focuses on the grotesque elements in Edgar Allan Poe’s the “Black Cat” and Horace Scudder’s “The White Cat”. Poe’s story is highly embedded with a lot of grotesque elements from the beginning to the end. These elements were presented through strange characters, mysterious happenings, and degradation through death. Poe represents the struggle between the supernatural and the natural which he reinforces through the narrator who struggles to commit wrongdoings. Even in the mist of trying to restrict himself, the narrator still does not know what he did. In “The White Cat,” Scudder employs grotesque elements as well but his application is subtly done unlike Poe whose application is more pronounced. The underlying meaning of this short story is on the spell of enchantment. However, Scudder, like Poe, displays the supernatural events through the characters of the “fairies” who has magical power to change the once a beautiful princess to a white cat. Grotesque includes absurd and bizarre elements and pierces the conventional version of reality. However; in its ability to shock or offend, grotesque helps to expose the vulnerability in human depicted via these absurd element which will be explained in detail in the present study.